Work-Life Balance and Happiness: Driving Employee Performance in Kupang City - Manafe, David; Goetha, Selfiana; Firmansyah, Mariano (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2025)
This research aims to understand the role and relationship between work-life balance, happiness, and performance, as well as the influence of happiness as a mediating variable. Specifically, the study focuses on employees in Kupang City. It employs a quantitative and explanatory research method. The questionnaire was distributed to government and private sector employees working within Kupang City. Of the 132 questionnaires distributed, the data was further analyzed using SmartPLS 4. The findings illustrate a direct influence of the work-life balance variable on performance and happiness. Additionally, the happiness variable directly affects performance. The mediation test results indicate that the happiness variable can mediate the relationship between work-life balance and performance.